Perbandingan Pengetahuan Tentang Interaksi Makhluk Hidup dengan Lingkungannya dan Sikap Peduli Lingkungan - Shevyta Ryandani; Arwin Surbakti; Darlen Sikumbang (Universitas Lampung, 2018)
This study aims to compare the knowledge of the interaction between living things with their environment and environmental concern. Sampling used purpose sampling. The research design was ex post facto. The results of the t-test showed that the students' knowledge and environmental concern in the school area of the TNWK are higher than the schools in the city. The results of a simple linear regression test showed that there was a relationship between the knowledge of interaction between living things and their environment and environmental concern of students in the school area of the TNWK and schools in the city. The conclusion of this study was there was a difference between the knowledge of interaction between living things and their environment and the attitude of caring for the students in the school of the TNWK area and in the City. Penelitian ini bertujuan membandingkan pengetahuan tentang interaksi antara makhluk hidup dengan lingkungannya dan sikap peduli lingkungan peserta didik. Pengambilan sampel menggunakan purpose sampling. Desain penelitian adalah ex post facto. Hasil uji t menunjukkan pengetahuan dan sikap peduli lingkungan peserta didik di sekolah area kawasan TNWK lebih tinggi dibanding sekolah di kota. Hasil uji regresi linier sederhana menunjukkan terdapat hubungan antara pengetahuan interaksi makhluk hidup dengan lingkungannya dan sikap peduli lingkungan peserta didik di sekolah area kawasan TNWK maupun sekolah di Kota. Kesimpulan penelitian ini adalah terdapat perbedaan antara pengetahuan interaksi makhluk hidup dengan lingkungannya dan sikap peduli lingkungan peserta didik di sekolah area kawasan TNWK dan di Kota. Kata kunci : perbandingan, pengetahuan, sikap peduli lingkungan